История о первом императоре. Петр I: [для чтения взрослыми детям] / [Н.В. Астахова] - Астахова Наталия Вячеславовна (Белый город, 2003)
Экземпляры: ф.5 (2003) / Инвентарный номер: 46392 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: А 91 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)6-4